Deconstructing product design : exploring the form, function, usability, sustainability, and commercial success of 100 amazing products. - Lidwell, William, ....-; Manacsa, Gerry, ....- (Beverly : Rockport, 2009)
What makes a product successful? How it looks? The way it functions? Its ease of use? Or do factors like price and marketing dominate? In a quest to find answers to these questions, Deconstructing Product Designengages readers in a process of critically analyzing a diverse collection of 100 innovative products, from well-known classics to contemporary objects of desire. New in paperback, this books aims to support critical thinking about design, facilitate discovery of patterns of success (and failure) across products, and enable designers to apply lessons learned to their own design work. Experts from multiples design disciplines contribute commentary, including: -Robert Blaich, industrial design -Jill Butler, graphic design -Alan Cooper, technology design -Brock Danner, architecture -Kimberly Elam, graphic design -Donald Emmite, design history -Larimie Garcia, graphic arts -Scott Henderson, product design -Kritina Holden, human factors -Robert Kingslyn, graphic design -Jon Kolko, interaction design -Lyle Sandler, experience design Continue the deconstruction athttp://www.deconstructingproductdesign.com.